Recordar. Violación de derechos humanos: una mirada médica, psicológica y política by Paz Rojas. - Pérez-Sales, Pau (Torture Journal, 2018)
The text, published with the help of the University of Oslo, is a compilation of lectures and essays by Dr. Paz Rojas, a Chilean doctor, an international expert in the fight against torture, who at 85 years’ old, is still actively collaborating as Vice President of the Comite de Defensa de los Derechos del Pueblo [Committee in Defense of the Rights of People] (CODEPU). It will soon be 40 years since that November in 1980 when CODEPU was founded.